2020
DOI: 10.1042/bsr20201449
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA-720 may predict prognosis and diagnosis in glioma patients

Abstract: We enrolled 122 patients with glioma who received surgery treatment in our hospital from June 2010 to May 2012, and 60 healthy individuals. We found that the plasma miR-720 in the glioma group was significantly higher than that in the healthy control group (3.19±1.26 vs 0.98±0.65, P<0.001). The sensitivity and specificity were 71.3% (95%CI: 62.4%-79.1%) and 83.3% (71.5%-91.7%), respectively. The results indicated that the plasma miR-720 level was associated with tumor grade (t=104.418, P<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Through reading titles and abstracts, 401 studies were eliminated. Ultimately, after excluding five studies for incomplete data ( n = 3) or a small sample size ( n = 2), 18 eligible articles ( 28 , 34 36 , 47 60 ) containing 24 studies were employed for the meta-analysis. We depicted the flow diagram of the study screening according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) ( http://www.prisma-statement.org/ ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Through reading titles and abstracts, 401 studies were eliminated. Ultimately, after excluding five studies for incomplete data ( n = 3) or a small sample size ( n = 2), 18 eligible articles ( 28 , 34 36 , 47 60 ) containing 24 studies were employed for the meta-analysis. We depicted the flow diagram of the study screening according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) ( http://www.prisma-statement.org/ ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 19 Increasing levels of miR-720 was associated with glioma migration and invasion through downregulation of TARSL2, 20 predicting adverse prognosis. 21 In contrast, for breast cancer, miR-720 reportedly inhibited invasion and migration via directly targeting TWIST1, 22 suggesting the complicated functions of miR-720 in tumorigenesis. To date, very few studies of exosomal miR-720 are available and no study has so far explored the role of exosomal miR-720 in the context of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Chen an al. reported that the plasma miR-720 was associated with the tumor grade and associated with recurrence or development in patients with glioma but that the sensitivity and specificity results indicated that the diagnostic ability of miR-720 for glioma was only moderate [ 41 ]. This result raises the question of what methodological choices should be made when one wants to use miRNAs as diagnostic and/or monitoring tools for patients with tumors and more particularly gliomas.…”
Section: Discussionmentioning
confidence: 99%